Integrating trait multidimensionality, predation and autotomy to explain the maintenance of boldness. (August 2017) - Delnat, Vienna; Debecker, Sara; Stoks, Robby
Abstract : There is an ongoing debate on how personality types are maintained within populations. We tested, for the first time, the potential of trait multidimensionality and trait compensation, where prey compensate for the costs of one trait by relying more on another one, in maintaining variation in boldness within a population. We studied how four boldness-related traits and swimming escape performance covary and shape the probability of survival and autotomy of Ischnura pumilio damselfly larvae in an experiment with predatory dragonfly larvae. Our results did not support the common belief that bold individuals are selected against in terms of survival selection by predation. Instead, we found survival selection favouring individuals combining being bold for two boldness-related traits. The four boldness-related traits did not covary frequently, supporting the multidimensionality of boldness. Moreover, animals bolder for one trait (activity in the presence of predator cues) were shyer for another trait (response to predator cues), which indicated trait compensation. However, the support for trait compensation was limited. The only other case of trait compensation was that bold larvae compensated for their increased risk-taking behaviour in the presence of a predator with a higher probability of autotomy. These patterns may contribute to maintaining variation in boldness in damselfly populations. Just as boldness-related traits are multidimensional, the mechanisms underlying their persistence in natural populations are also likely to be multifaceted. Highlights: Mechanisms maintaining bolder animals within populations are not fully understood. We scored boldness traits and linked these to autotomy and mortality by predation. Boldness-related traits did not frequently covary, indicating multidimensionality. Bold individuals were not killed more by predators. Bold larvae relied more on autotomy to compensate increased risk-taking behaviour.